2014
DOI: 10.1371/journal.pone.0086910
|View full text |Cite
|
Sign up to set email alerts
|

Staurosporine and Extracellular Matrix Proteins Mediate the Conversion of Small Cell Lung Carcinoma Cells into a Neuron-Like Phenotype

Abstract: Small cell lung carcinomas (SCLCs) represent highly aggressive tumors with an overall five-year survival rate in the range of 5 to 10%. Here, we show that four out of five SCLC cell lines reversibly develop a neuron-like phenotype on extracellular matrix constituents such as fibronectin, laminin or thrombospondin upon staurosporine treatment in an RGD/integrin-mediated manner. Neurite-like processes extend rapidly with an average speed of 10 µm per hour. Depending on the cell line, staurosporine treatment affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…These data could indicate a different impact of SSP on specific kinases when used at various concentrations and for variable time periods [ 14 ]. In preliminary experiments, we have found that in the continuous presence of SSP, some glioma cell lines differentiate into PGCCs, although the majority of cell lines only expresses a highly branched cell morphology with neurite-like processes, as previously reported by us for SCLC and PC12 cells [ 17 , 26 ].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These data could indicate a different impact of SSP on specific kinases when used at various concentrations and for variable time periods [ 14 ]. In preliminary experiments, we have found that in the continuous presence of SSP, some glioma cell lines differentiate into PGCCs, although the majority of cell lines only expresses a highly branched cell morphology with neurite-like processes, as previously reported by us for SCLC and PC12 cells [ 17 , 26 ].…”
Section: Discussionsupporting
confidence: 70%
“…Flow cytometry was performed on a BD FACSCanto II instrument, and the data were analyzed with the FlowJo software. Cell cycle status was analyzed as already described [ 17 , 18 ]. Briefly, A549 cells were trypsinized, collected in PBS, fixed and permeabilised following BD BrdU Flow kit manufacturer's instructions, incubated with anti-human Ki67 FITC conjugated antibody (BD Pharmingen), and counterstained with DAPI to exclude debris and necrotic cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobile single human breast carcinoma cells show complex changes in their behaviour and morphology when cultivated in the presence of SSP. We have recently shown that SSP induces dramatic changes in cell morphology, such as the induction of neurite-like processes [ 12 ] or the formation of polyploid giant cells [ 14 ]. Therefore, we decided to cultivate single breast carcinoma cells in the presence of 50 nM of SSP ( Figure 3 ), the highest concentration that was still non-toxic (as tested with the LDH assay, see the Materials and Methods Section) for all three cell lines when cultivated on PL.…”
Section: Resultsmentioning
confidence: 99%
“…On the cellular level, SSP inter-alia interferes with cell migration, proliferation, differentiation, and survival in a multifaceted manner [ 10 , 11 ]. We recently have shown that SSP mediates the conversion of small-cell lung carcinoma (SCLC) cells into a neuron-like process-bearing phenotype [ 12 ], whereby the broad pattern of SSP-induced effects is more restricted, with different SSP analogs that exhibit higher substrate specificity [ 13 ]. In addition, SSP can also induce the reversible formation of resting giant cells, as demonstrated by us for A549 non-SCLC cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%